Repression of shade-avoidance reactions by sunfleck induction of HY5 expression in Arabidopsis - Sellaro, Romina Vanesa (2011)
The light environment provides signals that play a critical role in the control of stem growth in plants. The reduced irradiance and altered spectral composition of shade light promote stem growth compared with unfiltered sunlight. However, whereas most studies have used seedlings exposed to contrasting but constant light treatments, the natural light environment may exhibit strong fluctuations. As a result of gaps in the canopy, plants shaded by neighbours may experience sunflecks, i.e. brief periods of exposure to unfiltered sunlight. Here, we show that sunflecks are perceived by phytochromes A and B, and inhibit hypocotyl growth in Arabidopsis thaliana mainly if they occur during the final portion of the photoperiod. By using forward and reverse genetic approaches we found that ELONGATED HYPOCOTYL 5, LATE ELONGATED HYPOCOTYL, PHYTOCHROME KINASE SUBSTRATE 4 and auxin signalling are key players in this response.